Pesticide Management Bill and its Regulations - Priyanka, N.; Rajashekhar, M.; Akhil, G.; Asritha, C. H.; Keerthana, B.; Bharghavi, K. (Chronicle of Bioresource Management, 2024)
Pesticide management bill 2020 helps in safe supply of pesticides and reduces the risk to people, animals, and the environment, it aims to control the manufacture, import, sale, storage, distribution, use, and disposal of pesticides. This bill provides registration of pesticides at central government and compulsory licensing at state government. Insecticide inspectors appointed by the central or state governments are authorized to examine properties, seize documents, halt the sale or distribution of pesticides, and collect samples of pesticides for examination. This bill also helps in import and export of pesticides reduces its effect on humans, environment etc.